Analysis of Apriori Algorithm on Sales Transactions to Arrange Placement of Goods on Minimarket - Sukadiana Putra, Putu Bagus Indra; Suryani, Ni Putu Sri Merta; Aryani, Sri (International Journal of Engineering and Emerging Technology, 2018)
In the business world, business development is a very important factor to be reckoned with. This is done in order to always survive in the competitive world of business. Improving product quality, adding product types and reducing the company's operating costs are some things that can be done in order to survive in the competition. The thing that can be done to meet those needs is to perform sales transaction data analysis using Data Mining. One of the Algorithms that belongs to an association in Data Mining that matches is the Apriori Algorithm. A priori algorithm aims to find frequent item sets in a set of data. A priori algorithm defined a process to find a priori rules that meet minimum requirements for support and minimum requirements for confidence. This research seeks to develop a business strategy of placement of groceries that is adjusted to the consumer consumption pattern in minimarket. Thus, the arrangement of merchandise can be adjusted with the rules of association to fit the pattern of consumer consumption.